Feasibility analysis model for construction of soccer stadiums - Serageldin, Mohamed Zakaria (AUC Knowledge Fountain, 2018)
This current research aims to study the different stadiums worldwide and to analyze the different aspects controlling them in terms of planning, design and construction. In this regard, there have been radical changes in the stadium projects approach over the last 30 years. In the past, soccer stadiums used to be consisted of only a pitch and a seating area for the fans. However, over the last 30 years, an evolution started to take place in utilizing stadiums as economically beneficial projects. Currently, stadiums have all safety requirements and incorporate the latest technological advances in order to achieve maximum efficiency. Furthermore, studying stadiums from different continents concentrates on the positive and negative aspects of these stadiums including different stadiums worldwide. That is an attempt to reach a viable solution to develop successful stadiums in terms of planning, design and construction. Therefore, the main goal of this study is finding a way to have a safe stadium that can generate profits to its owner plus the prospect of finding different funding options that could be used effectively. In this study, the analysis will focus on cost, safety and profitability of each stadium project. Then, we will begin to implement our own created model for a new stadium to be built in Egypt, or any other country worldwide using the Big Mac Index. We will take into consideration the whole process of establishing a new successful soccer stadium project, starting by setting a vision, planning, design and then construction.